2013
DOI: 10.2174/1874210601307010094
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ultrasonic Bone Surgery (Piezosurgery) to Surgically Treat Bisphosphonate-Related Osteonecrosis of the Jaws (BRONJ). A Case Series Report with at Least 1 Year of Follow-Up

Abstract: This preliminary work documents the use of a powerful piezosurgery device to treat biphosphonate-related osteonecrosis of the jaw (BRONJ) in combination with classical medication therapy. Eight patients presenting 9 BRONJ sites were treated, 2 in the maxilla and 7 in the mandible. Reason for biphosphonate (BiP) intake was treatment of an oncologic disease for 5 patients and osteoporosis for 3. The oncologic and osteoporosis patients were diagnosed with BRONJ after 35-110 months and 80-183 months of BiP treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
0
14
0
2
Order By: Relevance
“…Moreover, the cavitation effect together with antibiotic therapy seems to be suitable to decrease the microbial aggregation involved in BRONJ process [35]. …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the cavitation effect together with antibiotic therapy seems to be suitable to decrease the microbial aggregation involved in BRONJ process [35]. …”
Section: Resultsmentioning
confidence: 99%
“…Some authors have proposed a fluorescence-guided (Pautke et al, 2011a) or piezosurgical procedure (Blus et al, 2013), but those were not applied in our study, which had a success rate of 83.6% within the average follow-up of 23.5 months (Table 5). This study demonstrated the prognostic value of the UCONNS for predicting the outcome of ONJ surgery beyond the primarily intended dentoalveolar surgery under BP therapy.…”
Section: Management Of Osteonecrosismentioning
confidence: 96%
“…In terms of surgical management of ONJ, innovative techniques such as ultrasonic piezoelectric bone surgery have produced encouraging results, combining less invasive surgical access and superior healing process (Blus, Giannelli, Szmukler-Moncler, & Orru, 2017;Blus, Szmukler-Moncler, Giannelli, Denotti, & Orru, 2013).…”
Section: Optimising Surgical Managementmentioning
confidence: 99%